2021
DOI: 10.3390/math9222857
|View full text |Cite
|
Sign up to set email alerts
|

SEIR Mathematical Model of Convalescent Plasma Transfusion to Reduce COVID-19 Disease Transmission

Abstract: In some diseases, due to the restrictive availability of vaccines on the market (e.g., during the early emergence of a new disease that may cause a pandemic such as COVID-19), the use of plasma transfusion is among the available options for handling such a disease. In this study, we developed an SEIR mathematical model of disease transmission dynamics, considering the use of convalescent plasma transfusion (CPT). In this model, we assumed that the effect of CPT increases patient survival or, equivalently, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The simplest and most popular fundamental model is the SIR model [ 16 , 17 , 18 ], which describes the change in population in the system through differential equations by dividing the population into three classes: susceptible class , infected class , and recovered class . A more complex model is also available where populations are grouped into multiple statuses with increased disease control factors, such as vaccination control [ 19 ] and convalescent plasma transfusion [ 20 ]. In 2020, Din et al [ 21 ] developed a mathematical model for COVID-19 in Thailand which divided the population into six classes, namely, the SLIQHR model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simplest and most popular fundamental model is the SIR model [ 16 , 17 , 18 ], which describes the change in population in the system through differential equations by dividing the population into three classes: susceptible class , infected class , and recovered class . A more complex model is also available where populations are grouped into multiple statuses with increased disease control factors, such as vaccination control [ 19 ] and convalescent plasma transfusion [ 20 ]. In 2020, Din et al [ 21 ] developed a mathematical model for COVID-19 in Thailand which divided the population into six classes, namely, the SLIQHR model.…”
Section: Introductionmentioning
confidence: 99%
“…They studied the latent population, which is an asymptomatic group, but vaccination control was not considered. In 2021, Husniah et al [ 20 ] demonstrated the SEIR model of convalescent plasma transfusion as a control to reduce the spread of COVID-19. The effect of convalescent plasma transfusion helps to increase patient survival [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 𝑆𝐼𝑅 compartment mathematical model was presented by Kermack and McKendrick in 1927 as the first epidemic model [18]. Further, it become the foundational model in research on the transmission of COVID-19, and the mathematical concept involved in Kusumo et al [19], Husniah et al [20], Kurniawan et al [7], Sihotang et al [21], Fatmawati et al [22], Husniah et al [23], and Nuraini et al [24]. Then, a quarantine policy and isolation are used to design a mathematical model by Manaqib et al [8], Ali et al [9], Batista et al [10], Musafir et al [11], and Khan et al [12], to investigate the spread of the corona disease.…”
Section: Introductionmentioning
confidence: 99%
“…The greater value of the parameter of PSBB is given, the faster the COVID-19 disease will disappear. [8] construct a mathematical model related to COVID-19 disease to determine the effectiveness of convalescent plasma therapy without distinction among mild, severe, and critical infected people. The result showed that the effect of giving convalescent plasma therapy could reduce the spread of COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%